Creating a Strategic Energy Reduction Plan. - Offermann, Scott (River Publishers, 2021)
This book provides a simple, easily followed process for auditing building operations to identify and reduce energy consumption that leads to measurable carbon reduction. The crucial steps of this process involve assessing the facility⁰́₉s current conditions, understanding, and analyzing the operational and cost-based opportunities that increase carbon output. Taking this information to report the findings and then document a multiyear energy and carbon reduction plan. The book discusses the full scope of building components and systems, including how each system affects energy efficiency. It describes the operational energy efficiencies that are gained by implementing no-cost changes or alternative maintenance activities already funded. The book includes the process for identifying capital improvement opportunities, along with evaluating return on investment and life cycle replacement options for equipment. The four-step process described in this book will serve as a valuable tool for every building operator seeking to improve energy performance and reduce carbon output.
Keywords: Buildings -- Energy conservation -- Handbooks, manuals, etc.; Energy auditing -- Handbooks, manuals, etc.; elektronické knihy; electronic books